Wireless Sensor and Actuator Networks for Smart Cities - Sema Oktug (Ed.); Burak Kantarci (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Our lives are being transformed by the interplay between mobile networks, wireless communications, and artificial intelligence. This transformation is an outcome of the emerging Internet of Things (IoT) concept and advancements in computer architecture that translate into high computing power, high-performance processing, and huge memory capacities. In addition to the IoT, cyber-physical systems aim for the seamless integration of physical systems with computing and communication resources. Furthermore, in urban areas, the integration of “software-defined sensor networks” and “sensing as a service” concepts with legacy WSN-based systems is leading to the transformation of conventional city services towards smart cities. Smart energy, smart driving, smart homes, smart living, smart governance, and smart health are just a few services that smart cities can offer. This book focuses on novel solutions for wireless sensor and actuator networks in smart cities. This Special Issue invites academic and industry researchers in computer science and engineering, electrical engineering, and communication engineering, as well as ICT industry engineers and practitioners, to contribute original articles in all aspects of wireless sensor networks and actuator systems for smart cities.